DETERMINASI PENYALURAN KREDIT BANK UMUM DI INDONESIA PERIODE 2006-2009 - Dias Satria; Rangga Bagus Subegti (University of Merdeka Malang, 2010)
Banking sector plays a significant role in promoting a sustainable economic development. Its role wasimportant in ensuring the banking intermediary function to distribute money flow from deficit unit tosurplus unit. The analysis of the banking intermediary function was important to ensure the effectiveness ofthe monetary policy instrument, such as: SBI. The model of panel regression would be developed in thispaper to analysis some factors affecting bank loans in Indonesia. The objective was to understand thebehavior of bank loans in Indonesia